2007
DOI: 10.1063/1.2713352
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ferroelectric bismuth lanthanum nickel titanate thin films by rf magnetron sputtering

Abstract: The epitaxial growth, structural properties, and ferroelectric properties of bismuth lanthanum nickel titanate (Bi1−xLax) (Ni0.5Ti0.5)O3 (BLNT) thin films deposited on Pt(100)∕MgO(100) substrates by rf magnetron sputtering have been investigated using x-ray diffraction, transmission electron microscope, and polarization–electric field hysteresis loop measurements. The ferroelectric BLNT(00ℓ) phase with c-axis orientation and a single-phase tetragonal perovskite structure appeared at x⩾0.3. The tetragonality (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…MS has been used to grow a variety of epitaxial oxides of interest as optical waveguides, [217] light emitters, [218][219][220][221] capacitor dielectrics, [222,223] high-T c superconductors, [224][225][226][227][228] photocatalysts, [229] gas sensors, [83] ferroelectrics, [230][231][232][233] piezoelectrics, [46,234] conductive oxides, [235][236][237][238][239] gate dielectrics, [29,[240][241][242][243][244] magnetoresistive materials, [245][246][247][248][249][250][251][252][253][254][255][256][257] general purpose insulators, [258,259] magnetic insulators, [260,261...…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…MS has been used to grow a variety of epitaxial oxides of interest as optical waveguides, [217] light emitters, [218][219][220][221] capacitor dielectrics, [222,223] high-T c superconductors, [224][225][226][227][228] photocatalysts, [229] gas sensors, [83] ferroelectrics, [230][231][232][233] piezoelectrics, [46,234] conductive oxides, [235][236][237][238][239] gate dielectrics, [29,[240][241][242][243][244] magnetoresistive materials, [245][246][247][248][249][250][251][252][253][254][255][256][257] general purpose insulators, [258,259] magnetic insulators, [260,261...…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…This combination of peaks has frequently been observed for many types of deposition processes. 16,18,42,[51][52][53] There are no other peaks relevant to TiO 2 and Bi 2 O 3 , such as Bi 12 TiO 12 , and Bi 2 TiO 7 . 55 Post-annealing at 450 • C sharpened both peaks, indicating improved crystallization of the film.…”
Section: Resultsmentioning
confidence: 99%
“…For such a reason, the fabrication of the single-phase perovskite structure thus far has been difficult by lots of thin-film preparation methods such as sol-gel [3], metalorganic chemical vapor deposition (MOCVD) [4] and pulsed laser deposition (PLD) [5]. We have succeeded in the fabrication of c-axis oriented perovskite (Bi 1-x La x )(Ni 0.5 Ti 0.5 )O 3 compound films by high-temperature sputtering in accordance with the concept that when the lanthanum oxide with a large bond dissociation energy (BDE) [6,7] value of 9 eV is sputtered, a stable twelvefold coordination geometry of O 2-(LaO 12 ) is formed around the A sites, and simultaneously, Bi 3+ cation with a small ionic radius of 0.102 nm [8] is incorporated into the A site vacancies designed in advance in the perovskite crystal, as described in our previous papers [9,10]. Moreover, it was confirmed that the fabricated (Bi 0.5 La 0.5 )(Ni 0.5 Ti 0.5 )O 3 (BLNT) film exhibited apparent ferroelectricity, and had a remanent polarization (P r ) value of 12 C/cm 2 and a coercive field (E c ) value of 148 kV/cm.…”
Section: Introductionmentioning
confidence: 91%